Detoxifying effect of pyridoxine on acetaminophen-induced hepatotoxicity via suppressing oxidative stress injury. (April 2018) - Roh, Taehyun; De, Umasankar; Lim, Seong Kwang; Kim, Min Kook; Choi, Seul Min; Lim, Duck Soo; Yoon, Sungpil; Kacew, Sam; Kim, Hyung Sik; Lee, Byung-Mu
Abstract: The detoxifying effect of pyridoxine against acetaminophen (APAP)-induced hepatotoxicity was investigated. HepG2 cells were co-treated with APAP and pyridoxine to compare with betaine or methionine for 24 h. LDH, ALT and AST activities were measured to determine direct cells damage in vitro and in vivo. Lipid peroxidation, antioxidant enzymes activity, and glutathione level were measured. Cytochrome c releaseand procaspase-3, cleaved caspase-3, Bcl-2, or Bax protein levels were measured to determine APAP-induced apoptotic cell death. Pyridoxine treatment significantly increased cell viability and decreased leakage of LDH activity against APAP-induced hepatotoxicity in HepG2 cells. ALT and AST activities were dose-dependently reduced by pyridoxine treatment compared to APAP-treated group. Significant increases in activities of GST and GPx were observed after co-treatment with APAP and pyridoxine. Although APAP-induced Nrf2 and HO-1 expression levels were gradually reduced in HepG2 cells by pyridoxine treatment, induction of antioxidant enzymes activities were dose-dependently increased. These protected effects of pyridoxine against APAP-induced hepatoxicity were closely associated with suppression of APAP-induced oxidative stress and apoptotic cell death in HepG2 cells. These data indicated that the protective action of pyridoxine against hepatic cell injuries was involved in the direct antioxidant activity which provides a pivotal mechanism for its potential hepatoprotective action. Highlights: Pyridoxine decreased LDH, ALT and AST activities against APAP-induced hepatotoxicity in vitro and in vivo. Increases in antioxidant enzymes (GST and GPx) and GSH levels were observed after co-treatment with APAP and pyridoxine. Cytochrome c and procaspase-3, Bcl-2, or Bax protein levels were measured to determine APAP-induced apoptotic cell death. The protective action of pyridoxine against hepatic cell injuries was involved in the direct antioxidant activity. Pyridoxine showed protective activity via HO-1 induction serving as a key player in APAP-induced cell survival pathway.